Avaliação de custo-utilidade do tratamento da Artrite Reumatoide oferecido no SUS-MG - Grazielle Dias da Silva (2016)
Rheumatoid arthritis (RA) is a chronic disease that affects about 1% of the adult population. This study aimed to carry out an assessment of cost-utility analysis of treatment for RA in in the state of Minas Gerais (MG) with the following specific objectives: i. systematic review and meta-analysis focusing on monoclonal antibodies (AM) used in the treatment of the RA; ii. assessment of patients spending profile that received high cost of medicaments for the treatment of RA in SUS/MG in the period 2008-2013; and iii. evaluation of cost-utility of treatment for RA offered in SUS/MG. Methods: We conducted a systematic review and meta-analysis on the treatment of RA. Then a historical cohort study of all drug users for the treatment of RA of MG between 2008-2013. We opted for the perspective of public financing for the evaluation of direct health expenditures. For the analysis of the factors that influenced the total spending on drugs, we used the multiple linear regression analysis. The alternatives Adalimumab and Etanercept were compared through a cost-utility analysis. Effectiveness and utility data collected in an open prospective cohort study that followed patients with RA were used. Spending values were obtained from the historical cohort and the economic evaluation was performed using TreeAge Pro 2014 program. The Markov model was established in six-month cycles, with a time horizon of five years. Discount rate applied to 5% and the sensitivity analysis was performed. Results: Were included 55 articles in Systematic Review. The meta-analysis for ACR best outcome pointed for the groups treated with monoclonal antibodies (MA+MTX) when compared with groups treated with MTX alone. In a historical cohort study were identified 11,573 individuals. The majority were women with an average age of 52 years. Multivariate analysis showed a negative relationship between increased spending and age, female and diagnostic, and positive relationship to the variables IDH-M and the use of anti-TNF. The cost-utility analysis showed that, despite the high persistence rates observed for six and twelve months of treatment, the chances of success were low. There was no significant difference to gain in effectiveness between the groups. Treatment with ETA (±DMARD) was more expensive after 5 years of follow-up and the treatment with ADA (±DMARD) was more cost-effective. The sensitivity analysis indicated that the results are sensitive to changes in the cost of treatment ETA (±DMARD). Conclusions: In this study we observed that treatment regimens containing MA associated with MTX are more effective than the same alone. It was observed that this expense is influenced by characteristics such as gender and age of patients, in addition to sociodemographic conditions. Compliance with the treatment protocol proposed by the Ministry of Health was observed. The cost-utility analysis also pointed to some factors that can impact both the success of the therapy and in the costs for the health system. It also indicated that both therapeutic alternatives can be interesting from the point of view of the public manager when the PCDT is correctly applied.